Inggris - Yusari , Rita; Novita, Rita; Syarfuni; Mayang Sari, Siti (Jurnal Dikdas Bantara, 2025)
Mathematics learning in elementary schools often faces challenges in improving students' conceptual understanding, especially in fractions. A fifth-grade teacher at Sd Negeri 61 Banda Aceh City, Mrs. N, said in an interview session that during the teaching and learning process in the classroom, teachers still tend to use lecture methods as is generally used so that the teaching and learning process in the classroom is conventional and lacks creativity during learning, students are unable to implement it into real life. The Realistic Mathematics Education (RME) approach provides a solution by connecting mathematical concepts with real-life contexts, making it easier for students to understand and apply fraction concepts more meaningfully. This study aims to analyze the implementation of the RME model in fraction learning and its effect on elementary school students' conceptual understanding. The research method used is a quasi-experimental study with a pretest-posttest control group design. The research subjects consisted of fifth-grade elementary school students who were divided into an experimental group (with RME) and a control group (with conventional methods). The research instruments included conceptual understanding tests, observations, and interviews to obtain quantitative and qualitative data. The results showed that students who learned with the RME approach experienced a more significant increase in conceptual understanding compared to students who learned using conventional methods. RME-based learning can help students construct fraction concepts through exploration of contextual situations, group discussions, and reflection on problem-solving strategies. Therefore, using this approach can be an effective strategy in improving the quality of fraction learning in elementary schools.